Effect of Steam Explosion on Structural Characteristics of β−Conglycinin and Morphology, Chemical Compositions of Soybean Meal - Kong, Feng; Zeng, Qinghua; Li, Yue; Guo, Xingfeng (Frontiers in Nutrition, 2022)
Steam explosion was applied as a means to degrade β-conglycinin and the changes of morphology, chemical compositions of soybean meal and structural characteristics of β-conglycinin were investigated in this study. Results showed that steam explosion at 0.7 MPa for 8 min could effectively decrease the β-conglycinin content of soybean meal while the histamine content was not increased. The structural characteristics of soybean meal proteins were analyzed by SDS-PAGE, FTIR, CD and XRD, steam explosion caused the degradation of high weight proteins and reduced the band density of α′, α and β subunits in β-conglycinin. The micro-surface of soybean meal seemed to be in the cracked or puffed stage and the color became brownness or darkness after steam explosion. Steam explosion facilitated the dissolution of water-extractable arabinoxylans, which is 4.81 folds higher than that of native soybean meal. And the phytic acid was exposed to hydrothermal environment of steam explosion process and consequently degraded by 12.95%~24.69%. DPPH radial scavenging activity of soybean meal extract was gradually increased from 20.70% to 33.71% with the rising of treated pressure from 0.3 MPa to 0.7 MPa, which was 1.11~1.81 folds of native extract. Steam explosion may be a new modification technology that could decrease antigenicity, and the steam exploded soybean meal (0.7 MPa, 8 min) with lower β-conglycinin and phytic acid content could be widely used in food products.